Influência dos polimorfismos associados aos genes OPG, RANK, RANKL e HIF1A na anquilose da articulação temporomandibular - Corso, Paola Fernanda Cotait de Lucas (2018)
Temporomandibular joint (TMJ) ankylosis is an uncommon and complex disease with a multifactorial or unknown etiology that has a great negative impact on of individuals. The aim of this study was to evaluate the association between polymorphisms in regulatory genes of bone metabolism, such as OPG, RANK, RANKL and HIF1A in individuals with TMJ ankylosis. The sample consisted of 181 individuals, of both genders, age ranging in TMJ ankylosis group from 6 to 57. Seventeen individuals with TMJ ankylosis and 164 controls. The DNA was extracted from oral cells. The genotyping of the genetic polymorphisms in OPG (rs2073618), RANK (rs3826620), RANKL (rs9594738) and HIF1A (rs2301113 and rs2057482) was performed by real-time PCR using TaqMan™ technology (Applied Biosystems). The data were submitted to statistical analysis with a level of significance less than or equal to 0.05. The OPG (rs2073618) polymorphism was associated with the TMJ ankylosis, both in the additive model and in the dominant model (p < 0.05). In the additive model, when the individuals carried the CC genotype, they presented 10.80 times more chance to develop the condition [p = 0.03/ OR: 10.80 (1.13 - 102.52)]. In the dominant model, individuals that carry at least one C allele are 5.76 times more likely to have TMJ ankylosis than those with the G allele [p = 0.01/ OR: 5.76 (1.42 - 23.25)]. The other genes did not present association with ankylosis (p > 0.05). The polymorphism associated with rs2073618 in OPG is a possible marker associated with the risk for the manifestation TMJ ankylosis.